1985
DOI: 10.1172/jci111820
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of a human alveolar macrophage-derived neutrophil-activating factor.

Abstract: Human alveolar macrophages (AM) were obtained from eight normal volunteers using fiberoptic bronchoscopic lavage to explore potential interrelationships among leukocytes in pulmonary defense against infection. AM placed in monolayer tissue cultures released material into culture supernatants with the capacity to enhance the bactericidal capacity of human neutrophils. Neutrophils preexposed to supernatants killed Pseudomonas aeruginosa from 70 to 90% more efficiently than control cells (P < 0.02). AM culture su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Some of the above reports as well as our present data clearly indicate that the neutrophil-activating peptides released by mononuclear phagocytes are distinct from the two well-known monokines, IL-1 and tumor necrosis factor (TNF) . Several of the NAF-like molecules were shown to be considerably smaller than either monokine (26,28,30,31), and to exert effects that could not be obtained with recombinant and highly purified monokines (31) . In addition, amino acid sequencing of purified NAF (8) showed no significant structural homology with IL-la and ß and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the above reports as well as our present data clearly indicate that the neutrophil-activating peptides released by mononuclear phagocytes are distinct from the two well-known monokines, IL-1 and tumor necrosis factor (TNF) . Several of the NAF-like molecules were shown to be considerably smaller than either monokine (26,28,30,31), and to exert effects that could not be obtained with recombinant and highly purified monokines (31) . In addition, amino acid sequencing of purified NAF (8) showed no significant structural homology with IL-la and ß and TNF-a.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged cigarette smoking, in addition to other, well known risks, is often associated with the accumulation of pulmonary alveolar macrophages that are larger than in nonsmokers (Miiller and Hirschberg 1984), have an enhanced cytotoxic potential for normal lung parenchymal cells in vitro ) and, mainly with the help of complement component C5 (Robbins et al 1987), can attract (Hunninghake etal. 1978;Hunninghake and Crystal 1983) and activate (Pennington et al 1985) neutrophils. It seems safe, therefore, to accept that cigarette smoking may damage the alveolar epithelium (Jones et al 1980), at least in part, by the cytotoxic effects of phagocytes.…”
Section: Inhaled Noxious Agentsmentioning
confidence: 99%
“…We have previously demonstrated that alveolar macrophages (AM) placed in monolayer tissue cultures release a substance which enhances the bactericidal capacity of human neutrophils [32]. Neutrophils pre-exposed to supernatants killed Pseudomonas aeruginosa 70-90% more efficiently than control cells.…”
Section: Interactions Between Macrophages and Granulocytesmentioning
confidence: 99%